Role of modified biophysical profile in the management of post term pregnancy - Singh, Somya; Rai, Seema; S., Prajwal; Rao, P. S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Prolonged gestation complicates 5% to 10% of all pregnancies and confers increased risk to both the fetus and mother. In the west about 18% of all singleton pregnancies persist beyond 41 weeks, 10% (range, 3% to 14%) continue beyond 42 weeks and 4% (range, 2% to 7%) continue beyond 43 completed weeks in the absence of an obstetric intervention. The risks for prolonged and post-term pregnancy include obesity, nulliparity, maternal age >30 years. Apart from these racial and ethnic differences have also been cited to be the reasons for higher risk of prolonged and post-term pregnancy. Post term pregnancies are associated with various maternal and neonatal complications. Methods: A prospective study was carried out at Department of Obstetrics and Gynaecology, Command Hospital, Central Command, Lucknow. 100 patients were selected and divided into two groups and were followed up till the delivery. Data so collected was subjected to analysis using Statistical Package for Social Sciences version 15.0. Results: Majority of women enrolled in the study were aged above 25 years. Majority of women enrolled in the study were primigravida (67%). The Mean BMI of women enrolled in the study was 24.2±3.43 kg/m2 and the expectant and control groups were matched demographically and anthropometrically. The compromised modified biophysical profile was recorded in 33 (66%) of women in expectant group. Rate of caesarean delivery was 30% in expectant and 46% in control group. In the expectant group, AFD was the most common indication for caesarean section while control group had NPOL as the most common indication for caesarean section. In the expectant group, mean AFI showed a declining trend with increasing gestational age. Conclusions: It was concluded that expectant management using modified biophysical profile (MBPP) does not provide an additional value over prophylactically managed pregnancies. Although cesarean rate and NICU admission rates were lower in expectant group as compared to control group yet the utility of MBPP in expectant management could not be proven and needs further assessment in larger studies or pooled clinical trials.